STUDY ON THE QUALITY OF BROILER CHICKEN MEAT IN A MODERN MARKET IN SUKOHARJO REGENCY - Aldianto, Aldianto; Windyasmara, Ludfia; Purwati, Catur Suci (Universitas Nusa Cendana, 2024)
The total number of broiler chickens in Sukoharjo district was 9,134,244, with the overall provincial production in Central Java reaching 225,048,936. The quality indicators of broiler meat include water content, soluble protein and cooking shrinkage of the meat. The research was conducted in a modern market located in Sukoharjo district from Superindo, Transmat, Lottemart and Hypermart markets. Samples taken were breast part and sampled using the RAL method. The observed variables were drip loss, cooking loss, soluble protein and fat lavels.The data were analysed using analysis of variance (ANOVA) and Duncan's multiple range test (DMRT). The results of the study on broiler meat in different markets were found to be significantly different (P < 0.01) for dripping loss, cooking loss and soluble protein. However, no difference was observed in meat fat content (P > 0.05).The findings of the study indicate that the quality of broiler meat in modern markets in Sukoharjo district has an impact on drip loss, cooking loss and soluble protein, but not to any significant extent on fat lavels.